Persepsi Guru dalam Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) di SD IT Adzkia 3 Padang - M. Luthfi Bayu; Ismira Ismira; Hendrizal Hendrizal (Lembag, 2025)
This study aims to analyze teachers' perceptions of the implementation of the Projek Penguatan Profil Pelajar Pancasila (P5) at SD IT Adzkia 3 Padang. The research is motivated by differences in teachers' perceptions of P5 and the fact that P5 is a new initiative in Indonesia's educational curriculum, designed to integrate the values of Pancasila into students' character through a project-based approach. This study employs a descriptive qualitative method, with data collection techniques including in-depth interviews, observations, and document analysis. The data analysis technique used in this research involves data collection, reduction, display, and verification. The research subjects consist of teachers directly involved in the implementation of P5 at the school. The results of the study indicate that most teachers have a good understanding of the goals and importance of P5 in shaping students' character in line with Pancasila values. However, some teachers have yet to fully comprehend P5, with several issues identified, such as inconsistencies in the implementation of P5 in classrooms, excessive administrative burdens, and a lack of information regarding P5. The study concludes that teachers need to improve their time management and learning to address these challenges. Additionally, stronger support from the school and government.